PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KOMPETENSI DASAR MENYIAPKAN SPT TAHUNAN PPH WAJIB PAJAK ORANG PRIBADI - Ratri Seto Karyaning Utami, ; Eko Suprayitno, (Pendidikan Ekonomi, 2012)
The goal of this study are : 1) to find out the teacher activities by applying the direct learning model in preparing the Annual Income Tax Individual Tax Payer 2) to find out the students activities by applying the direct learning model in the basic competencies Preparing the Annual Income Tax Individual Tax Payer  3) to find out the students learning outcome toward the employment of direct learning model in the basic competencies Preparing the Annual Income Tax Individual Tax Payer. This class action research (PTK) is done in three cycles. The data collecting technique is done by doing the observation, documentation, test and questionnaire. Based on the collected data and the discussion, it can be concluded that theres an enhancement of the teacher in managing the learning process. From the 1st, 2nd and 3rd cycle with the aspect value 2,8; 3,5; and 4,2, whilst the students activities also increased with the aspect value 2,5; 3,4; and 4. The students learning outcome achievement in the 1st cycle is 76, and increase in the 2nd cycle 79,32 and 84 in the 3rd cycle. From the students response questionnaire, it is found that 71% of the students are agree on the application of the direct learning model in the basic competencies Preparing the Annual Income Tax Individual Tax Payer